Political communication of the capital placement in NTT Gubernatorial election - Bataona, Mikhael Rajamuda; Riang, Yoseph; Silaban, Donna Isra; Leuape, Emanuel Sowe; Nggili, Agnes Lidia Herlina (Jurnal Kajian Komunikasi, 2025)
Background: This study is driven by concerns over the political practices seen during the 2024 NTT gubernatorial election. It examines political communication strategies, particularly how political capital was used by both candidates and voter groups. The study assumes that political capitalization does not always have positive dimensions; in this election, some forms of political capital were aggressively traded. Goals: To map the political modalities present during the election, analyze how candidates’ political modalities were distributed through political communication activities, and describe the symbolic rivalry among voter groups shaped by these modalities. Methods: This study employs a critical paradigm and uses a case study approach. Field data were gathered through in-depth interviews with 27 relevant informants, along with document observation related to the research focus. Pierre Bourdieu’s theory of “Modalities” is applied to critically analyze the realities of the research subject. Results: In the 2024 NTT gubernatorial election, each candidate pair relied on distinct political modalities: Melki–Johni emphasized economic capital, Ansy–Jane mobilized symbolic capital through millennial and female representation, and Simon–Andrianus drew upon ethnic identity. Voter groups also reflected this stratification—upper-class voters leveraged financial and business capital, the middle class relied on educational and political capital, and lower-class groups contributed numerical strength. Political rivalries, rooted in religion and ethnicity, further shaped communication practices, expressed both directly and symbolically. Conclusion: The 2024 NTT gubernatorial election was marked by political communication strategies that relied on capitalizing various political modalities in transactions between candidates and voter groups. This use of political modalities also generated political rivalries within society. Implications: The research findings may provide a basis for recommendations on transforming political culture—particularly during electoral contests—to support the development of local political life and democracy.